Expanding the possibilities of electrografting modification of voltammetric sensors through two complementary strategies. (1st October 2019) - Pérez-Ràfols, Clara; Rosal, Miguel; Serrano, Núria; Ariño, Cristina; Esteban, Miquel; Díaz-Cruz, José Manuel
Abstract: Two different modification strategies by means of aryl diazonium salt electrografting were compared for the development of voltammetric sensors. In this sense, l -cysteine was immobilized onto a screen-printed carbon-based electrode surface through either its –NH2 or its –COOH group and the performance of the resulting modified sensors was tested for the simultaneous determination of Pb(II) and Cd(II) by anodic stripping voltammetry. The results obtained indicate that attachment through the –COOH group of cysteine, despite being a much less frequent electrografting strategy, improves the analytical performance of the resulting sensor achieving lower LODs, at low μg L −1 levels, for Cd(II) and Pb(II). Furthermore, this strategy allows the quantification of both metal ions below the legal limits established by the European Water Framework Directive, which represents a great improvement with respect to similar sensors reported in the literature. Graphical abstract: Image 1 Highlights: l -Cystine was immobilized on SPCNFE following two strategies based on aryl diazonium salt electrografting. Better analytical performance is achieved when using the electrografting through the –NH2 group. LOD and LOQ at μg L −1 levels were achieved for the simultaneous determination of Pb(II) and Cd(II) ions.